A fuller picture: evaluating an art therapy programme in a multidisciplinary mental health service. Issue 1 (26th September 2016) - Brady, Catherina; Moss, Hilary; Kelly, Brendan D
Abstract : Art therapy has a long history in mental healthcare, but requires an enhanced evidence base in order to better identify its precise role in contemporary services. This paper describes an evaluation of an art therapy programme in an acute adult psychiatry admission unit in Ireland. A mixed method research design was used. Quantitative data were collected through a survey of 35 staff members and 11 service users. Qualitative data included free text comments collected in the survey and individual feedback from service users. Both methods aimed to assess the role of art therapy as part of a multidisciplinary mental health service. Thematic content analysis was employed to analyse qualitative data. Staff demonstrated overwhelming support for art therapy as one element within multidisciplinary services available to patients in the acute psychiatry setting, Qualitative feedback associated art therapy with improvements in quality of life and individual support, and emphasised its role as a non-verbal intervention, especially useful for those who find talking therapy difficult. Creative self-expression is valued by staff and service users as part of the recovery process. Recommendations arising from the research include continuing the art therapy service, expanding it to include patients under rehabilitation, provision of information and education sessions to staff, and further research to identify other potential long-term effects. The low response of staff and small sample in this study, however, must be noted as limitations to these findings.